Study of harmonic RFID : chipless RFID - Huang, Zhong Xi. (2010)
This final year project report summarizes the study and work that had been done during the past 7 months. The objective of this project is to have a thorough understanding of Radio Frequency Identification (RFID) technology and design a 6-bit chipless RFID tag. The study and research that have been carried out in this project includes the idea of using Radio Frequency Identification technique as a wireless data capturing technique for automatic identification in many areas such as inventory tracking, retail chains, security surveillance and so on [ 1 ]; the concept design and fabrication of chipless RFID transponder using spiral microstrip resonators; the principle and design of spiral microstrip resonators for narrow-bandstop filters. Design and simulation of spiral microstrip resonators for narrow-bandstop filters was done by computer-aided simulation software Advance Design System 2009 (ADS2009). The measurement of spiral microstrip resonators was done by Agilent E5061A and N5230A network analyzer. The six-bit chipless RFID tag was designed and fabricated. The simulated and measured results were evaluated. The objectives of this project were fulfilled.